Isotherm parameter library and evaluation software for CO2 capture adsorbents. (5th December 2020) - Ga, Seongbin; Lee, Sangwon; Kim, Jihan; Lee, Jay H.
Abstract: We developed a computer-aided evaluation software system for CO2 capture adsorbents, named General Adsorbent Library and Evaluation (GALE). This software, freely available for downloads, provides two practical functions: an extensive sorbent library with isotherm parameters for more than 2000 sorbents and a computationally efficient function to evaluation their performance for user in a pressure swing adsorption (PSA) process. The new sorbent library provides isotherm parameters, which were calculated through molecular simulations using the previously available structure libraries. Based on these parameters in the software, performances of user-selected adsorbents can be evaluated and ranked in terms of the CO2 capture efficiency in an ideal PSA process. The evaluation function is designed to address diverse situations such as varying feed conditions and target purities. Some innovative strategies regarding the use of purity upper bound and candidate pool reduction concepts are suggested to lower the computational load.